A review of potential areas of construction cost estimating and identification of research gaps - Toh, Tien Choon; Ali, Kherun Nita (Faculty of Built Environment, UTM, 2008)
The models structure of construction cost and price forecasting underlie all the techniques being used and yet until quite recently, industry has still not getting familiar with their attributes and characteristics. Without a good comprehension of the various types of cost model, effective cost control and the development of future forecasting techniques are studied. The central theme of this paper is that cost estimating financial and non-financial information includes all the information which quantity surveyors and estimators need to manage effectively to lead their firms to competitive success. However, the specific role of cost estimating in the quantity surveying and contracting firms differ depending on the firm’s competitive strategy, organizations, and the management functions to which cost estimating is applied. Meanwhile, changes in the business environment have amended the nature of competition and the types of techniques that quantity surveyors and estimators use to succeed in their businesses including globalization, advances in construction technologies, advances in information technologies, the internet and e-commerce, client centered, new forms of management organization, and changes in the social, political, and cultural environment of business. As a result, some of the relevant potential areas of construction cost estimating have been recognized and being discussed further in this article.